Análise químico-farmacêutica de rosuvastatina cálcica comprimido e cápsula - Ângelo, Marilene Lopes (2016)
Rosuvastatin calcium is a synthetic statin used to treat hypercholesterolemia, inhibiting 3-hydroxyl-3-methylglutaryl coenzyme A (HMG-CoA) reductase. In Brazil, this drug is widely marketed as tablets and compounded capsules. However, there is no method described in official compendia for the mentioned dosage forms. This work proposed the development and validation of methods for quantitative analysis of rosuvastatin calcium (high performance liquid chromatography and spectrophotometry) and dissolution tests (also performed in biorelevant medium) for capsules and tablets forms. The stability of rosuvastatin calcium and the impact of polymorphism on the release of this drug in capsule formulations were also evaluated. The methods of quantitative analysis didn't present statistical difference for the significance level of 5% In the study of forced degradation of rouvastatin calcium, it was observed its instability against acid and photolytic degradations. The products of degradation generated by the stress conditions were characterized. After, the method was used in order to evaluate real samples. Different formulations for immediate release were produced with commercial raw material (amorphous solid). The obtained formulations were analyzed for the development of dissolution tests using the crystalline form M of rosuvastatin calcium. This form were recrystallized in our laboratory and showed a lower aqueous solubility when compared to the amorphous form. The formulation with this crystalline form also showed a slow dissolution rate that demonstrates the impact of the polymorphism on this molecule when prepared as capsule form. In addition to identifying different solid forms, the discriminant test developed was able to discriminate formulations with different compositions of excipients. A dissolution test was developed and validated for the tablets form. This method was used to comparasion of similar products related to the reference. The results proved that there is similar release characteristics for two of three similar products, in comparison with the reference product Crestor®. A study using milk at pH = 6.4, as biorelevant medium, was conducted by using the same apparatus and rotation conditions of the discriminatory assay. The results showed that both evaluated pharmaceutical forms presented the same specification suggested for the medium using phosphate buffer pH = 6.8. Thus, the developed methods contribute to quality, therapeutic safety and efficacy evaluation of rosuvastatin calcium, and to expand the scientific knowledge related to this statin.